GESTATIONAL DIABETES MELLITUS AMONG WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - Shamsher, Huda; Aziz, Moizza; Aslam, Rakhshanda; Idrees, Umbreen; Riaz, Misbah; Kauser, Mamoona (Journal of Ayub Medical College Abbottabad, 2024)
Background: Gestational diabetes mellitus is defined as a carbohydrate intolerance of pregnancy, which complicates pregnancy and is associated with the adverse effects on the mother and her fetus. Hormonal disturbances together with insulin insensitivity that is characteristic of women with Polycystic Ovarian Syndrome (PCOS) place them at high risk of developing metabolic complications such as GDM. Nevertheless, the specific prevalence of GDM in women with PCOS is still not confirmed, especially concerning different population groups. The objectives of this work include assessing the prevalence of GDM in pregnant women with PCOS, as well as examining related risk factors, and discussing its practical and theoretical implications. Methods: A retrospective observational study of 400 women of childbearing age with PCOS using the Rotterdam Criteria were included from a tertiary hospital between 2018 and 2023. Diabetes mellitus type GDM was diagnosed using the American Diabetes Association (ADA) criteria based on the 75 gm oral glucose tolerance test (OGTT). Data on basic demographic, clinical features such as age, BMI, diabetes family history, and phenotype of PCOS were collected. Chi-square tests and logistic regression were used to test frequencies and the relationship between GDM and PCOS-relevant characteristics. Results: The prevalence of GDM in the women with PCOS screen positive was overall 37.5%. Combined, subgroup analysis of the nine studies showed that the prevalence of HAIR-ANN was significantly higher in the following groups: Obese women (55%); Women with age 35 years or more (48%); And women with PCOS, hyperandrogenic phenotypes (40%). The prevalence of GDM in the studied cohort of women with PCOS was 18.5% which was significantly higher than in a matched non-PCOS control group; aOR 2.8; 95%CI 1.9–4.1. Both BMI and insulin resistance were found to be significant predictors of GDM in PCOS subjects. Conclusion: This observation was particularly evident with regards to women with PCOS, suggesting the importance for screening and early management initiatives are developed for GDM. They found that priority interventions which should be focused on this high risk group are; routine monitoring of their blood glucose, pre conception weight control measures and client specific care plans. Moreover, it is a recommendation for firmer outcomes than longitudinal studies of the efficiency of GDM preventive approaches in individual with PCOS.